NEED OF DEVELOPMENTAL EDUCATION FOR SUSTAINABLE DEVELOPMENT - Mondal, Sweta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Knowledge and Skills are essential pillars to promote sustainable development. The global context of education has brought a new focus to development education for an inclusive sustainable future. Education for Sustainable Development addresses global equity, justice, and sustainability issues. To address these global issues, Educational Interventions are necessary to attain sustainability. Educational Interventions builds skills of analysis and understanding, efficiency with a need to promote sustainability and justice. Sustainability includes a wide range of parameters including environmental factors, social and cultural factors, which can only be attained by creating awareness and empower learners to take responsibility to bring a change only through education. This can be attained through development education which is needed to address the inequalities and social injustice. It creates awareness of global injustice, helps to create a critical thinking of the global challenges, and apply an analytical thinking to the thought process to bring a social change. The key goals of ESD are holistic education, create stakeholders’ awareness, participation and cooperation of all and building capacity of the stake holders. This paper proposes the purpose of Education for Sustainable Development and what transformation can be bought about through this developmental education to attain sustainability.